Pengaruh Penggunaan Beberapa Jenis Abu terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Media Gambut - Muhammad Ali Fahmi Situmorang; Al Ichsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to determine effect of the use several types of ash on the growth oil palm seedlings on peat media and determine the best type of ash for oil palm seedlings on peat media. The research has been implemented on land technical service unit (UPT) and soil analysis at Laboratory of soil science Faculty of Agriculture, University of Riau, Bina widya college km 12,5, simpang baru, Tampan,Pekanbaru. The research was conducted from august to November 2017. The research eksperimentally using a completely randomized design (CRD) consists of 6 treatments and 4 replications, and obtains 24 experimental units,each experimental unit consists of 2 seeds, and the total is 48 seeds. Data obtainable from observations were analyzed statistical using analysis of varian (ANOVA). The results of variance analysis continued with Duncan’s multiple range test at the 5% level. Observation parameters of seedling height,number of leaves,increase in bulb diameter,root volume,root canopy ratio,weight dry seed and soil chemical properties. The results of giving some kind ash that has a real effect for the height of the seedlings and the increase of leaves and the best treatment at the provision of oil palm empty fruit bunches ash which showed the highest yield on seedling height of 23,52cm,root canopy ratio of 2,70g and the weight dry of seedlings is 22,27g.Keyword : Oil Palm, Type of Ash, Peat